Molecular epidemiology and phylogenetic analysis of human papillomavirus infection in women with cervical lesions and cancer from the coastal region of Ecuador - Bedoya Pilozo, Cesar H. (2017)
The aim of the present study was to gather information regarding the molecular epidemiology of Human papillomavirus (HPV) and related risk factors in a group of women with low- and high-grade cervical lesions and cancer from the coastal region of Ecuador. In addition, we studied the evolution of HPV variants from the most prevalent types and provided a temporal framework for their emergence, which may help to trace the source of dissemination within the region. We analyzed 166 samples, including 57 CIN1, 95 CIN2/3 and 14 cancer cases. HPV detection and typing was done by PCR-sequencing (MY09/MY11). HPV variants and estimation of the time to most recent common ancestor (tMRCA) was assessed through phylogeny and coalescence analysis. HPV DNA was found in 54.4% of CIN1, 74.7% of CIN2/3 and 78.6% of cancer samples. HPV16 (38.9%) and HPV58 (19.5%) were the most prevalent types. Risk factors for the development of cervical lesions/cancer were the following: three or more pregnancies (OR = 4.3), HPV infection (OR = 3.7 for high-risk types; OR = 3.5 for HPV16), among others. With regard to HPV evolution, HPV16 isolates belonged to lineages A (69%) and D (31%) whereas HPV58 isolates belonged only to lineage A. The period of emergence of HPV16 was in association with human populations (tMRCA = 91. 052 years for HPV16A and 27. 000 years for HPV16D), whereas HPV58A preceded Homo sapiens evolution (322. 257 years). This study provides novel data on HPV epidemiology and evolution in Ecuador, which will be fundamental in the vaccine era.